Dance sport movement therapy in the metaverse: A new frontier for alternative mental health therapies - Radanliev, P (SAGE Publications, 2024)
This paper investigates the integration of Dance Movement Therapy (DMT) within extended reality (XR) environments, exploring its potential as a non-pharmacological intervention for mental health conditions. The study employed a blend of qualitative evidence synthesis and analyses of primary quantitative data, focusing on the therapeutic implications of Dance in virtual, augmented and mixed realities. Data from wearables and sensors on movements, physiological responses and emotional feedback are analysed using AI/ML algorithms, including Random Forest, SVM, CNNs and RNNs. The research highlighted the importance of data privacy and ethical considerations, emphasising the need for securely storing metadata to ensure user trust and legal compliance. Findings underscored the potential of XR environments like the Metaverse in transforming mental health practices, offering efficient, engaging and effective therapeutic interventions. The study also introduced the novel concept of Physical Intensity Matching and the significance of personalised exercise selection. Despite its ground-breaking insights, the research acknowledged potential biases introduced by wearables and the challenges of ensuring data accuracy. This paper is a foundational exploration into the convergence of DMT, XR and AI, paving the way for future interdisciplinary research in mental health and technology.